Phlebotomy loss in sick newborns admitted in neonatal intensive care unit - Tyagi, Neha; Rai, Ruchi; Kumar Singh, Dharmendra; Bhakhri, Bhanu Kiran (International Journal of Contemporary Pediatrics, 2023)
Improved neonatal care has resulted in increased survival of neonates and duration of hospital stay. These sick neonates are subjected to frequent diagnostic blood sampling. Phlebotomy loss (PL) is acknowledged as one of the primary factors leading to anaemia in critically ill infants.